Estimated number of replications for evaluation of productive and morphologic characters in soybean genotypes - Cargnelutti Filho, Alberto; Gonçalves, Elaine Cristine Piffer (Comunicata Scientiae, 2011)
Estimating the number of repetitions of data obtained from several experiments performed in given location is important to minimize human and financial resources and leverage the existing information. The objective of this research was to determine how many evaluations (replications) were necessary to predict productive and morphologic characters of soybean genotypes (Glycine max L. Merril) and to verify its variability in the number of replications among characters. Twenty-eight soybean genotypes were evaluated in five experiments conducted in Jaboticabal, São Paulo State, Brazil, from 2002 to 2005. Randomized blocks design with three repetitions was installed to evaluate the following productive characters (seed yield, number of pods per plant and mass of one hundred grains) and morphologic (plant height at maturity, height of first pod insertion, number of nodes per plant and number of branches per plant). It was performed analysis of variance, estimated the repeatability coefficient and calculated the number of repetitions necessary to predict the real value of the genotypes. It was found variability in the number of replications among the productive and morphologic characters. Experiments with three replicates identify soybean genotypes with higher 17.52% (height of first pod insertion) to 61.07% (number of nodes per plant) of real accuracy. To improve the accuracy of the evaluation of characters in soybean plants, you need to use a greater number of repetitions.